2013
DOI: 10.1093/europace/eus388
|View full text |Cite
|
Sign up to set email alerts
|

Implantable cardioverter defibrillator therapy in paediatric practice: a single-centre UK experience with focus on subcutaneous defibrillation

Abstract: AimsSudden cardiac death (SCD) risk can be managed by implantable cardioverter defibrillators (ICD). Defibrillation shocks can be delivered via ICD generator and/or intracardiac or subcutaneous coil configurations. We present our single-centre use of childhood ICDs. Methods and resultsTwenty-three patients had ICD implantation, with median age and weight of 12.96 years and 41.35 kg. Indications included eight long QT; four hypertrophic cardiomyopathy; three Brugada syndrome; two idiopathic ventricular fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 24 publications
0
23
0
4
Order By: Relevance
“…Griksaitis et al 14 reported on S-ICD use in 23 children, and Pettit et al 13 reported on its use in 9 children (all on the left side of the thorax), with no difference in rates of pocket hematoma, infection, or inappropriate shocks compared to standard transvenous systems. Use of an S-ICD in a young patient who requires ICD placement is appealing because it avoids the need for transvenous leads, thus potentially averting venous occlusion and the notable risk of lead extraction in the event of lead failure or fracture 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Griksaitis et al 14 reported on S-ICD use in 23 children, and Pettit et al 13 reported on its use in 9 children (all on the left side of the thorax), with no difference in rates of pocket hematoma, infection, or inappropriate shocks compared to standard transvenous systems. Use of an S-ICD in a young patient who requires ICD placement is appealing because it avoids the need for transvenous leads, thus potentially averting venous occlusion and the notable risk of lead extraction in the event of lead failure or fracture 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The indications for defibrillation therapy as primary prevention remains controversial, and the decision to implant an ICD in an asymptomatic child has often made it more difficult (5). Improvements in the risk stratification of diseases such as hypertrophic cardiomyopathy and recognition of genetic disorders such as long-QT syndrome and the number of pediatric patients selected for defibrillator implantation have increased over the years (4).…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous array leads with an abdominally placed active can gives an option for the implantation of these devices in infants and patients with a limited venous access, such as repaired congenital heart disease, or loss of venous access, such as thrombosis, and preserved vasculature and reduced lead-related complications, which is frequently observed during childhood (5). There is no clear methodology for the implantation of defibrillator systems, particularly in small children and infants.…”
Section: Discussionmentioning
confidence: 99%
“…However, although smaller leads for smaller people may be nice, they are clearly not essential. Perhaps subcutaneous ICD systems can improve the set of options available for younger patients or result in superior performance, 8 but rigorous trials are needed, 9 and trials are currently underway. Delaying the initial implantation of a transvenous system may have significant benefit greater than just the actuarial number of years.…”
Section: Article See P 2393mentioning
confidence: 99%